Red fox immune-gene sequences - Donaldson, Michael E.; Rico, Yessica; Hueffer, Karsten; Rando, Halie M.; Kukekova, Anna V.; Kyle, Christopher J. (Dryad Digital Repository, 2017)
Red fox immune-gene sequences (2,229,152 bp) used to design the sequence capture assay.